2017
DOI: 10.15578/jppi.22.3.2016.173-180
|View full text |Cite
|
Sign up to set email alerts
|

Dinamika Perubahan Metode Penangkapan Rawai Tuna Di Samudera Hindia

Abstract: Rawai tuna merupakan salah satu alat tangkap penting bagi industri perikanan di Indonesia. Target utama alat tangkap ini adalah ikan tuna yang mempunyai nilai ekonomis penting seperti tuna mata besar dan madidihang. Penelitian ini bertujuan untuk mengetahui karakteristik kapal dan perubahan metode penangkapan rawai tuna di Indonesia. Pengumpulan data dilakukan oleh pemantau ilmiah (observer) pada kapal rawai tuna yang berbasis di Pelabuhan Benoa Bali, mulai Agustus 2005 hingga November 2014. Pemantau ilmiah me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Based on these morphological characteristics, it shows that the bycatch sharks landed during the research at Benoa Harbor are 1) blue sharks, 2) longfin mako sharks, 3) fine hammerhead sharks, 4) sharks that have similar characteristics with the fine hammerhead shark, 5) the short-finned mako shark, 6) the big eye thresher shark and 7) the cowboy shark. According to Jatmiko et al (2019), from 2013-2016, at least seven species of sharks were found, namely Prionace glauca, Isurus oxyrinchus, Carcharhinus longimanus, Hemipristis elongata, Sphyrna spp., Carcharhinus falciformis dan Alopias spp.…”
Section: Morphological Identificationmentioning
confidence: 99%
“…Based on these morphological characteristics, it shows that the bycatch sharks landed during the research at Benoa Harbor are 1) blue sharks, 2) longfin mako sharks, 3) fine hammerhead sharks, 4) sharks that have similar characteristics with the fine hammerhead shark, 5) the short-finned mako shark, 6) the big eye thresher shark and 7) the cowboy shark. According to Jatmiko et al (2019), from 2013-2016, at least seven species of sharks were found, namely Prionace glauca, Isurus oxyrinchus, Carcharhinus longimanus, Hemipristis elongata, Sphyrna spp., Carcharhinus falciformis dan Alopias spp.…”
Section: Morphological Identificationmentioning
confidence: 99%